Bibliometric and visualization analysis of research trend in mental health problems of children and adolescents during the COVID-19 pandemic - Guo, Zeming; Zhang, Yiran; Liu, Qin (Frontiers in Public Health, 2023)
Objectives: To find the revolutionary changes and new trends of studies in mental health problems of children and adolescents during the COVID-19 pandemic. Methods: The literature obtained from the web of science core collection as of June 28, 2022, was analyzed using citespace, vosviewer bibliometric visualization mapping software. Results: A total of 6039 relevant papers were found, of which 5594 were included in the study. The number of literatures is growing since 2020; and the country, institution, and journal publications were analyzed. The co-citation analysis shows that there are more research articles among the highly cited articles and a lack of systematic reviews that use critical thinking for review. In the cluster analysis, mental health and life change were the most representative. The timeline view of the keywords shows that Online learning (#0), Public health (#1), and Mental health (#2) are the three largest clusters and shows the change over time. Conclusion: This study helped analyze the mental health of children and adolescents during the COVID-19 pandemic and identified hot trends and shortcomings, which are important references for the theoretical basis of future research and decision making and technical guidance for systematic reviews.